Phenotypic and Genotypic Analysis of Antimicrobial Resistance of Commensal Escherichia coli from Dairy Cows’ Feces - Maksud Kerluku, Marija Ratkova Manovska, Mirko Prodanov, Biljana Stojanovska-Dimzoska, Zehra Hajrulai-Musliu , Dean Jankuloski and Katerina Blagoevska (Licensee MDPI, Processes, 2023)
Abstract: Commensal Escherichia coli has the potential to easily acquire resistance to a broad range of antimicrobials, making it a reservoir for its transfer to other microorganisms, including pathogens. The aim of this study was to determine the prevalence of resistant commensal Escherichia coli isolated from dairy cows’ feces. Phenotypic resistance profiles and categorization were determined by minimum inhibitory concentration (MIC) testing with the broth microdilution method, while the PCR method was used to determine the presence of resistant genes. Out of 159 commensal E. coli isolates, 39 (24.5%) were confirmed to have resistance. According to the MIC values, 37 (97.3%) and 1 (2.7%) isolate were phenotypically categorized as ESBL and ESBL/AmpC, respectively. All isolates showed resistance to ampicillin, while 97.4%, 56.4%, and 36% showed resistance to cefotaxime, ciprofloxacine, and azitromycine, respectively. Not all isolates that showed phenotypic resistance were found to be carrying the corresponding gene. The most prevalent resistant genes were gyrA, tetA, sul2, and tetB, which were present in 61.5%, 64%, 54%, and 49% of the isolates, respectively. The results clearly indicate that, besides their resistance to multiple antimicrobials, the commensal E. coli isolates did not necessarily carry any genes conferring resistance to that particular antimicrobial.
Keywords: ESBL; AmpC; commensal E. coli; MIC; resistance; dairy cow; feces